Relationship between personal lifestyle, fast food industries and development in technology and communication with consumption habit of fast food among Generation Y in Sudong Melaka Sdn Bhd / Remunay Frank Apal - Frank Apal, Remunay (Faculty of Business and Management, 2019)
Fast food is one type of food that able to prepare in short time period and sell to customer in reasonable price. This type of food was introduce at western countries and begins at Asian near recent decade. Meanwhile, the group of generation Y was grown and subsequently become the largest age group that earn income for own or family’s expenses. Therefore, this research is conducted to study fast food consumption habit among generation Y in Sudong Melaka Sdn Bhd. Consumption habit of fast food among Generation Y acted as the dependent variable that is expected to be affected by personal lifestyle, fast food industries and development in technology and communication. In this study, respondent was the active staffs which also known as the Customer Care Officers of Sudong Sdn Bhd, Malacca. The respondent’s data were keyed into the Statistical Package for Social Sciences (SPSS) software to run the test for the analysis and interpretation purpose. After the data undergo few analysis, it was found that only fast food industries has a significance relationship with the consumption habit of fast food among generation Y in Sudong Melaka Sdn Bhd.